Liposomal Copermeation Assay Reveals Unexpected Membrane Interactions of Commonly Prescribed Drugs - Odehnalová, Klára; Balouch, Martin; Storchmannová, Kateřina; Petrová, Eliška; Konefał, Magdalena; Zadražil, Aleš; Berka, Karel; Brus, Jiří; Štěpánek, František (Molecular pharmaceutics, 2024)
The permeation of small molecules across biological membranes is a crucial process that lies at the heart of life. Permeation is involved not only in the maintenance of homeostasis at the cell level but also in the absorption and biodistribution of pharmacologically active substances throughout the human body. Membranes are formed by phospholipid bilayers that represent an energy barrier for permeating molecules. Crossing this energy barrier is assumed to be a singular event, and permeation has traditionally been described as a first-order kinetic process, proportional only to the concentration gradient of the permeating substance. For a given membrane composition, permeability was believed to be a unique property dependent only on the permeating molecule itself. We provide experimental evidence that this long-held view might not be entirely correct. Liposomes were used in copermeation experiments with a fluorescent probe, where simultaneous permeation of two substances occurred over a single phospholipid bilayer. Using an assay of six commonly prescribed drugs, we have found that the presence of a copermeant can either enhance or suppress the permeation rate of the probe molecule, often more than 2-fold in each direction. This can have significant consequences for the pharmacokinetics and bioavailability of commonly prescribed drugs when used in combination and provide new insight into so-far unexplained drug-drug interactions as well as changing the perspective on how new drug candidates are evaluated and tested.
Keywords: Lipid Bilayers; liposomy; Phospholipids; liposomes; léky na předpis; fluorescence quenching; Prescription Drugs; Humans; buněčná membrána; Fluorescent Dyes; fosfolipidy; Liposomes; drug interaction; Permeability; partitioning coefficient; permeability; lipidové dvojvrstvy; fluorescenční barviva; Cell Membrane; lidé; permeabilita